2019
DOI: 10.1111/tra.12632
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of cytosolic‐facing pools of diacylglycerol in budding yeast

Abstract: Diacylglycerol (DAG) is a key signaling lipid and intermediate in lipid metabolism. Our knowledge of DAG distribution and dynamics in cell membranes is limited. Using live‐cell fluorescence microscopy we investigated the localization of yeast cytosolic‐facing pools of DAG in response to conditions where lipid homeostasis and DAG levels were known to be altered. Two main pools were monitored over time using DAG sensors. One pool was associated with vacuolar membranes and the other localized to sites of polarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 104 publications
(231 reference statements)
1
27
0
Order By: Relevance
“…When cells in the stationary phase are diluted back to fresh medium, LDs are rapidly consumed for membrane expansion during cell proliferation. Previous studies have shown that LD resident lipases (Tgl3) are required for the lipolysis of TAGs to generate DAG and FAs (Ganesan et al, 2019;Kurat et al, 2006;Ouahoud et al, 2018). The resulting FAs in turn need to be activated by fatty acid activating enzymes to serve together with DAG as building blocks for the synthesis of membrane phospholipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cells in the stationary phase are diluted back to fresh medium, LDs are rapidly consumed for membrane expansion during cell proliferation. Previous studies have shown that LD resident lipases (Tgl3) are required for the lipolysis of TAGs to generate DAG and FAs (Ganesan et al, 2019;Kurat et al, 2006;Ouahoud et al, 2018). The resulting FAs in turn need to be activated by fatty acid activating enzymes to serve together with DAG as building blocks for the synthesis of membrane phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, LDs at Nuclear Vacuolar Junctions (NVJs) increase their TAG content using the activated FAs (Hariri et al, 2018(Hariri et al, , 2019. Upon growth resumption from the stationary phase, TAGs stored in LDs are rapidly broken down by LD resident lipases to release and channel DAGs and FAs towards the ER and the vacuole for membrane proliferation (Ganesan et al, 2019;Kurat et al, 2006;Markgraf et al, 2014;Ouahoud et al, 2018). Again, Faa4 is needed to reactivate the released FAs for membrane synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published results of membrane simulations show that high levels of DAGs are able to break the lamellar structure of the plasma membrane, reducing its integrity (28). Other research has shown that DAGs can be highly localised in specific areas of the membrane during cellular growth (29), potentially increasing the damage to the lamellar structure of the membrane. However, low concentrations of DAGs can replace ERG in membrane microdomains (30), making the membrane more rigid (11).…”
Section: Storage Lipidsmentioning
confidence: 99%
“…Because DAG is readily consumed in the synthesis of phospholipids and TAG, DAG generally represents a minor fraction of total membrane lipids (Ejsing et al, 2019). In growing yeast cells, however, DAG is enriched in the vacuolar membrane and a minor DAG pool resides in the ER membrane (Ganesan et al, 2019). The pool size and trafficking of DAG is also affected by other lipids including PS and also sphingolipid synthesis, which generates DAG (Figure 2A; Ganesan et al, 2019).…”
Section: Yeast Er-pm Contact Sites Represent a Nexus For Phospholipidmentioning
confidence: 99%
“…In growing yeast cells, however, DAG is enriched in the vacuolar membrane and a minor DAG pool resides in the ER membrane (Ganesan et al, 2019). The pool size and trafficking of DAG is also affected by other lipids including PS and also sphingolipid synthesis, which generates DAG (Figure 2A; Ganesan et al, 2019). In yeast strains defective in sphingolipid synthesis, DAG is primarily localized to the PM rather than the vacuolar membrane (Ganesan et al, 2019).…”
Section: Yeast Er-pm Contact Sites Represent a Nexus For Phospholipidmentioning
confidence: 99%